Performance and Health Decrements Associated With Relative Energy Deficiency in Sport for Division I Women Athletes During a Collegiate Cross-Country Season: A Case Series - Hooper, David R.; Mallard, Jared; Wight, Jeff T.; Conway, Kara L.; Pujalte, George G.A.; Pontius, Kelsey M.; Saenz, Catherine; Hackney, Anthony C.; Tenforde, Adam S.; Ackerman, Kathryn E. (Frontiers in Endocrinology, 2021)
The purpose of this case series was to evaluate the presence of low Energy Availability (EA) and its impact on components of Relative Energy Deficiency in Sport (RED-S) in a population of female collegiate runners. Seven female NCAA Division I athletes (age: 22.3 ± 1.5 yrs; height: 169.7 ± 5.7 cm; weight: 58.3 ± 4.1 kg) were tracked from August until February, covering the beginning (Pre XC), end (Post XC) of their competitive cross country season, and beginning of the following track season (Pre Track). The athletes were assessed for female athlete triad (Triad) risk, energy availability, body composition, resting metabolic rate (RMR), nutritional intake, and blood markers (including vitamin D, ferritin, and triiodothyronine (T3)). From Pre XC to Post XC there were no significant differences in body mass, fat free mass or body fat percentage. At Pre XC, mean EA was 31.6 ± 13.3 kcal/kg FFM∙d-1. From Post XC to Pre Track, there was a significant increase in body mass (59.1 ± 5.1 to 60.6 ± 5.7 kg, p<0.001,d=0.27). From Post XC to Pre Track, there was a significant increase in RMR (1466 ± 123.6 to 1614.6 ± 89.1 kcal·d-1, p<0.001,d=2.6). For 25(OH) vitamin D, there was a significant reduction from Pre XC to Post XC (44.1 ± 10.6 vs 39.5 ± 12.2 ng·mL-1, p=0.047,d=-0.4), and a significant increase from Post XC to Pre Track (39.5 ± 12.2 vs. 48.1 ± 10.4 ng·mL-1, p=0.014,d=0.75). For ferritin, there was a trend towards a decrease from Pre XC to Post XC (24.2 ± 13.2 vs. 15.7 ± 8.8 ng·mL-1, p=0.07, d=-0.75), as well as a trend toward an increase from Post XC to Pre Track (15.7 ± 8.8 vs. 34.1 ± 18.0 ng·mL-1, p=0.08, d=1.3). No differences in T3 were observed across time points. Average Triad risk score was 2.3 ± 1.4. Notably, 5 of 7 athletes met criteria for moderate risk. Despite many athletes meeting criteria for low EA and having elevated Triad risk assessment scores, most were able to maintain body mass and RMR. One athlete suffered severe performance decline and a reduced RMR. Surprisingly, she was the only athlete above the recommended value for ferritin. Following increased nutritional intake and reduced training volume, her performance and RMR recovered. Changes in body mass and body composition were not indicative of the presence of other concerns associated with RED-S. This exploratory work serves as a guide for future, larger studies for tracking athletes, using RMR and nutritional biomarkers to assess RED-S.